PENGARUH CAPOEIRA TERHADAP HUBUNGAN LUAR NEGERI BRASIL-INDONESIA TAHUN 2003-2014 - Situmorang, Jeffri; Yelta, Den (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aim to explain how a product of culture from one nation can influence the relations between two nations. Brasil a country that is rich of cultural heritage aims to influence other nations by means of cultural diplomacy, mainly emphazise on soft power to enhance the its national standing on international scale. Capoeira a cultural product of Brasil, that has been declared as intangible heritage of the world by UNESCO, is rapidly growing internationally. In Indonesia although not as rapidly grow as in european countries, capoeira has make its place as another growing martial arts. This research aims to explain the influence of capoeira on bilateral relationship between Brasil and Indonesia.This research theoretically has built with sociological liberalism perspectives on International Relations and supported by cultural diplomacy theories. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Scope of this research is Capoeira’s influence on Brasil-Indonesia foreign relation.Researcher has formulated an answered-hypothesis which reveals the facts that after the first founding of capoeira grup in Indonesia, up until 2014, Brasil-Indonesia bilateral relations is increasing. After the first capoeira international event held in Jakarta on 2006, the number of agreement both nations formulate increasing from only three to twelve in just three years. The increase of trade volume and also other bilateral aspects while capoeira is growing proves that capoeira as Brasil’s means cultural diplomacy enhance the relationship between the two nations.Key words: Capoeira, Cultural Diplomacy, Bilateral Relations, Influence